2016
DOI: 10.11646/zootaxa.4107.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Redescription Cyrtodactylus lateralis (Werner) (Squamata: Gekkonidae) and Phylogeny of the Prehensile-tailed Cyrtodactylus

Abstract: We redescribe Cyrtodactylus lateralis (Werner) on the basis of new specimens. Cyrtodactylus lateralis is a prehensile-tailed species, known from scattered lowland to mid-elevation localities in northern Sumatra. The prehensile-tailed Cyrtodactylus are more speciose and have a wider distribution than previously thought. This group includes a mainland SE Asian clade consisting of C. elok, C. interdigitalis, and C. brevipalmatus and an insular clade containing C. durio, C. lateralis, C. nuaulu, C. serratus, C. sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…In such instances, it is usually during windy and/or rainy nights (perhaps forced down from higher up; Dring, 1979; authors personal observation). All species have a prehensile tail used as a climbing aid (Dring, 1979;Grismer, 2008;Harvey et al, 2016) and usually carried in a coiled, elevated position.…”
Section: Habitat Preferences and Ecotypesmentioning
confidence: 99%
“…In such instances, it is usually during windy and/or rainy nights (perhaps forced down from higher up; Dring, 1979; authors personal observation). All species have a prehensile tail used as a climbing aid (Dring, 1979;Grismer, 2008;Harvey et al, 2016) and usually carried in a coiled, elevated position.…”
Section: Habitat Preferences and Ecotypesmentioning
confidence: 99%
“…Cyrtodactylus rubidus from the Andaman Islands was recovered as the sister species of this group, but this relationship was only well-supported in the ML analysis (92/0.86), and thus it was excluded although it is likely the relationship is correct. Cyrtodactylus durio and С. lateralis are highly arboreal (Grismer et al 2010, Harvey et al 2016) and bear morphological adaptations for arboreality such as a prehensile tail carried coiled (Fig. 21) in an elevated position.…”
Section: Cyrtodactylus Lateralis Groupmentioning
confidence: 99%
“…Unfortunately, DNA sequence data of C. brevipalmatus was not available for this analysis. In Harvey et al (2016), phylogeny based on morphology with three species added to original hypothesis of Grismer et al (2010) supports a close relationship between C. elok and C. brevipalmatus with C. interdigitalis as a sister species to this clade. Therefore, adding of DNA sequence of C. brevipalmatus in further phylogenetic analysis is still required for discovering the phylogenetic position of C. brevipalmatus.…”
Section: Discussionmentioning
confidence: 78%
“…The first species was described based on specimens collected from Khao Luang National Park, Nakhon Si Thammarat Province (Smith 1923). To date, C. brevipalmatus is currently endemic to Thailand (Grismer 2008;Harvey et al 2016) and its distribution was reported in Tak, Nakhon Si Thammarat, Phetchaburi, Uthai Thani Provinces (Nabhitabhata et al 2004;Nabhitabhata and Chan-ard 2005;Chuaynkern and Chuaynkern 2012).…”
Section: Introductionmentioning
confidence: 99%